VisTACO: Visualizing Tabletop Collaboration - Tang, Anthony; Pahud, Michel; Carpendale, Sheelagh; Buxton, Bill (Interactive Tables and Surfaces 2010 (ITS 2010), 2010)
As we design tabletop technologies, it is important to also understand how they are being used. Many prior researchers have developed visualizations of interaction data from their studies to illustrate ideas and concepts. In this work, we develop an interactional model of tabletop collaboration, which informs the design of VisTACO, an interactive visualization tool for tabletop collaboration. Using Vis-TACO, we can explore the interactions of collaborators with the tabletop to identify patterns or unusual spatial behaviours, supporting the analysis process. VisTACO helps bridge the gap between observing the use of a tabletop system, and understanding users‟ interactions with the system.